In Situ Activation of Penile Progenitor Cells with Low-Intensity Extracorporeal Shockwave Therapy. Issue 4 (28th February 2017) - Lin, Guiting; Reed-Maldonado, Amanda B.; Wang, Bohan; Lee, Yung-chin; Zhou, Jun; Lu, Zhihua; Wang, Guifang; Banie, Lia; Lue, Tom F.
Abstract: Background: We previously reported that progenitor cells, or stem cells, exist within penile tissue. We hypothesized that acoustic wave stimulation by low-intensity extracorporeal shockwave therapy (Li-ESWT) would activate local stem or progenitor cells within the penis, producing regenerative effects. Aims: To study the feasibility of in situ penile progenitor cell activation by Li-ESWT. Methods: We performed a cohort analysis of young and middle-age male Sprague-Dawley rats treated with 5-ethynyl-2′-deoxyuridine (EdU) pulse followed by Li-ESWT. In addition, Li-ESWT was applied to cultured Schwann cells and endothelial cells to study the molecular mechanism involved in cell proliferation. Thirty minutes before Li-ESWT, each rat received an intraperitoneal injection of EdU. Li-ESWT was applied to the penis at very low (0.02 mJ/mm 2 at 3 Hz for 300 pulses) or low (0.057 mJ/mm 2 at 3 Hz for 500 pulses) energy levels. The endothelial and Schwann cells were treated with very low energy (0.02 mJ/mm 2 at 3 Hz for 300 pulses) in vitro. Outcomes: At 48 hours or 1 week after Li-ESWT, penile tissues were harvested for histologic study to assess EdU + and Ki-67 + cells, and cell proliferation, Ki-67 expression, Erk1/2 phosphorylation, translocation, and angiogenesis were examined in cultured Schwann and endothelial cells after Li-ESWT. Results: Li-ESWT significantly increased EdU + cells within penile erectile tissues ( P < .01) at 48 hours and 1 week. There were more cells activated in young animals than in middle-age animals, and the effect depended on dosage. Most activated cells were localized within subtunical spaces. In vitro studies indicated that Li-ESWT stimulated cell proliferation through increased phosphorylation of Erk1/2. Clinical Translation: The present results provide a possible explanation for the clinical benefits seen with Li-ESWT. Strengths and Limitations: The main limitation of the present project was the short period of study and the animal model used. Li-ESWT could be less effective in improving erectile function in old animals because of the decreased number and quality of penile stem or progenitor cells associated with aging. Conclusion: Li-ESWT activation of local penile progenitor cells might be one of the mechanisms that contribute to the beneficial effects of shockwave treatment for erectile dysfunction, which represents a non-invasive alternative to exogenous stem cell therapy.